Kashmir at the Nexus of Geopolitics: Reinterpreting Mackinder’s Heartland Theory in the Asian Security Dilemma - Mirela Imširović; Adnan Kapo; Georges Olemanu Lohalo; Souliya Mounnarath; Muhammad Mutawalli Mukhlis (NAJAHA, 2026)
The Kashmir issue is a long-standing international dispute with significant regional and global implications for contemporary relations, marked by episodic tensions, sovereignty questions, and humanitarian concerns. Despite decades of negotiations, sustained United Nations engagement, and bilateral dialogue, the issue remains unresolved, while the continued involvement of international regulatory systems reflects ongoing efforts to support regional stability and constructive dialogue. By revisiting Halford Mackinder’s Heartland theory, the paper highlights the strategic significance of Kashmir within the broader Asian geographical context and security dynamics. Located at the intersection of South Asia, Central Asia, and China’s western edge, Kashmir represents a crucial focal point for India and Pakistan, a condition that further contributes to the persistence and complexity of competing claims. Methodologically, the study uses a qualitative research design that combines analysis with contextual assessment. The methodological approach includes a review of classical geopolitical theory and an examination of Kashmir's strategic location between South and Central Asia. The findings highlight the enduring significance of Kashmir not only as a geographic and strategic pivot, but also as a region that exemplifies the complex interactions between regional actors and broader international dynamics. By integrating classical geopolitical insights with an understanding of contemporary strategic considerations, the paper provides a comprehensive perspective on why Kashmir continues to shape security, diplomacy, and strategic planning in Asia.